Methods for the morphological and functional evaluation of microvascular damage in systemic sclerosis - Ruaro, Barbara (Korean J Intern Med, 2015)
Systemic sclerosis is a connective tissue disease characterized by alterations in microvascular structure and function. In these patients, numerous studies have demonstrated a relationship between capillary morphology and peripheral blood perfusion. Nailfold videocapillaroscopy reveals the peripheral microvascular morphology and thus allows classification and scoring of capillary abnormalities with respect to different microangiopathy patterns (early, active, and late). Laser Doppler flowmetry and laser speckle contrast analysis can be used to estimate cutaneous blood flow through microvessels and to assess and quantify blood perfusion at peripheral sites. These two methods are also used to identify changes in digital blood perfusion after the infusion of vasodilators.